Aspergillus Mediastinitis Presenting as Superior Mediastinal Syndrome in an Immunocompetent Child. Issue 2 (February 2015) - Agarwal, Sikha; Das, Anirban; Gochhait, Debasis; Trehan, Amita; Srinivasan, Radhika; Singh, Meenu
<x xml:space="preserve">Abstract</x> We report a case of mediastinal mass caused by a fungal infection in an immunocompetent child. The patient presented with superior mediastinal syndrome along with a swelling in the chest wall. Cytology and culture demonstrated Aspergillus flavus. The child was treated with voriconazole, which resulted in clinical response.